DEVELOPMENT OF GOOGLE SITES APPLICATION OF DIVERSITY THROUGH CHILDREN’S DOLANAN TEMBANG IN CIVICS LEARNING - Tri Susilo Raharjo, Agung; Wibawa, Sutrisna; Susanto, Moh. Rusnoto; Arumsari, Mela Dina (International Journal of Engagement and Empowerment (IJE2), 2024)
Interactive multimedia development in elementary schools is significant, and the current technological progress has progressed very rapidly. The development of interactive multimedia based on the Google Sites application is significant because the development of appropriate learning will trigger students to be active and creative. This web-based Google Sites media is considered a simple learning media that teachers and students use and understand. In particular, it makes it easy for learners to understand the material during online learning. Tembang dolanan anak as a learning medium is very appropriate because it is easy to learn, and students are more entertained learning while singing. The Diversity that discusses the various cultural differences of Indonesia requires development in learning so that students are more interested and understand the material better. This activity analyzes how the online learning process uses Google Sites. The material presented is Civics Learning for grade IV SD. The activity method used is the descriptive qualitative method. The sample in this study was 15 students who had personal smartphones. The 15 students consisted  of 10 male and five female students, targeting grade IV students at SDN Keputran A. The results of this activity are 1) Google sites an effect on online learning, 2) According to the result of learning observation and interview results, students are interested in Google Sites Media because this media is efficient, 3) Students feel comfortable with the media of children’s folk song or tembang dolanan anak because during learning students are entertained and can be presented in the form of coloured text, images, video and audio